2017
DOI: 10.1016/j.nlm.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Possible positive effect of the APOE ε2 allele on cognition in early to mid-adult life

Abstract: HighlightsE4 carriers self reported more memory problems, but no objective differences found.E2 carriers performed slightly better on episodic memory test.E2 carriers were faster in a test of executive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
0
16
1
Order By: Relevance
“…The present largest single-sample study has not found any association between the ε2 allele and special cognitive ability across all age ranges (Marioni et al, 2016). Sinclair et al (2017) found that the ε2 allele showed positive outcomes on episode memory and executive function in early to mid-adult life (ages 23-67). In the present study, the APOE genotype was associated with general cognitive performance (MMSE and ADAS13 scores) in the MCI group, but was not associated with any cognitive domains in CN elders or MCI patients; this can be attributed to the small sample size in this study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The present largest single-sample study has not found any association between the ε2 allele and special cognitive ability across all age ranges (Marioni et al, 2016). Sinclair et al (2017) found that the ε2 allele showed positive outcomes on episode memory and executive function in early to mid-adult life (ages 23-67). In the present study, the APOE genotype was associated with general cognitive performance (MMSE and ADAS13 scores) in the MCI group, but was not associated with any cognitive domains in CN elders or MCI patients; this can be attributed to the small sample size in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…A large body of work has focused on the relationship between APOE genotype and AD pathology. Many prior studies have examined the structural and functional differences in the brain, particularly in the hippocampus, resulting from the presence of ε4 (Schuff et al, 2009;Wang et al, 2015;Sinclair et al, 2017). More recently, researchers have paid more attention to the impact of the APOE ε2 allele on the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The 3 allele displayed a competitive survival advantage sufficiently robust to result in the current predominance of the 3/3 genotype which is now found in over 60% of the US population, presumably because of its protection for memory loss and dementia in progressively older age ranges [23]. Similarly, the 2 allele mutated from the 3 allele about 200,000 years ago, but this protective allele has remained relatively rare with the homozygous 2/2 variant less than 1%, and the 3/2 heterozygote in about 11% of the population [144].…”
Section: Discussionmentioning
confidence: 99%
“…The average effect size of 4 status was non-significant across cognitive domains. Sinclair et al [144] studied 114 participants with the allelic combinations of 3/3 (39 subjects), 3/4 (27 subjects), 4/4 (15 subjects), 3/2 (26 subjects), and 2/2 (7 subjects). The primary outcome was performance on the Rey Auditory Verbal Learning Test (RAVLT).…”
Section: Mental Performance In Young Apolipoprotein 4 Carriers (Table 8)mentioning
confidence: 99%
“…The results from the power analysis were that testing 15 participants would provide at least 80% power to detect a significant difference between-groups with a corrected p-value of p < 0.05. Amongst those invited and subsequently consented to take part: 16 were e3/ e3 carriers (these comprised the e4− group); 11 were e3/e4 and 5 were e4/e4 (these comprised the e4+ group, totaling 16); 1 participant was an e2/e4 and excluded from analyses based on evidence that the e2 allele might be protective 58 Between the two groups, there were no significant differences in age, gender balance, NART IQ, MoCA score or years of education (Table 1). Nevertheless in the imaging analyses, gender was entered as a covariate.…”
Section: Methodsmentioning
confidence: 99%